Diversidade biológica e cultural na formação de professores de biologia - Santos, Isabela Mayara dos (2022)
Starting from the theses of actions towards the environment are, for the most part, that we seek to reflect on the context in this work if socially inclusive positions are related to social environments about biological diversity. The possibility of associations between singularities has been built for some years by Pagan (2009; 2018; 2020), in which we have investigated the characteristics that make us unique and respect for the specifics of others, lead to less sexist, sexist, homophobic and meritocratic attitudes, and may also be living or practices of coexistence with the others. As a result of this concern, we ask ourselves: Are there sociocultural profiles that point to indicators on which teachers and students are sensitive to biodiversity? Starting from this question, we seek in this work related to aspects of biological diversity and cultural diversity, without the scope of training biology teachers. An electronic instrument was used as a data collection instrument, whose action knows the personal and conforming data profile of the respondents; Regarding the ideas of biological diversity, they are divided into four categories: anthropocentric, biocentric, integrating and disintegrating; and their sensitivity about the prejudice and discrimination of Brazilian minority groups. 112 responses were obtained from biology students and professionals from Brazilian universities, over eighteen years of age, who consented to participate, accepting the definitions proposed in the TCLE. The responses were tabulated and entered the statistical analysis program Statistical Package for the Social Sciences (SPSS). As main results, significant positive correlations were observed between the biocentric category of biological diversity and the socioeconomic and inclusion/exclusion categories, which shows us that people who are more sensitive to class diversity and socioeconomic inequality, as well as to inclusive issues from distinct racial and ethnic groups, people with disabilities and LGBTQIA+, tended to be more biocentric. This data suggests the confirmation of our hypothesis of approximation between perceptions about cultural and biological diversity, which is especially shown in the context of understanding equitable interspecific interactions. We conclude that these associations open the way to emphasize a training of biology teachers that recognizes the rights of other species on the planet and provides (re)connection, (re)integration and diplomatic coexistence.